FimC binds to the promoter region of agn43 to modulate autoaggregation - Wang, Zhihao; Niu, Xiangpeng; Zhong, Ningyuan; Kong, Lanfang; Nawaz, Saqib; Zhang, Haiyang; Jiang, Wei; Liu, Yuanyuan; Tu, Jian; Han, Xiangan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAvian pathogenic Escherichia coli (APEC) infection causes high mortality in chicks and leads to significant economic losses in the poultry industry. During the initial infection, APEC colonizes host cells using type 1 fimbriae and subsequently forms biofilms, resulting in persistent and chronic infections. fimC is a chaperone protein associated with type 1 fimbriae and plays a crucial role in the assembly of fimbriae. However, its regulatory role in agn43-mediated autoaggregation remains unclear.MethodsBy constructing fimC gene mutant strains, the autoaggregation, motility, biofilm formation, and the adhesion and invasion ability to HD-11 cells were examined. The transcriptome and the electrophoretic mobility shift assay (EMSA) were used to screen and verify the regulation of fimC on downstream genes.ResultsThe results demonstrated that the lack of fimC, but not fimbriae, significantly increased autoaggregation (p < 0.001) while promoting the transcription of agn43 (p < 0.01). Transcriptomic analysis showed that the deletion of fimC caused significant changes in the gene transcription levels in a variety of pathways, such as flagellar synthesis, biofilm formation, quorum sensing, and bis-(3′-5′)-cyclic diguanylic acid (c-di-GMP) metabolism. Further investigation revealed that fimC directly interacted with the promoter region of agn43 and inhibited its transcription. In addition, both fimC and agn43 had regulatory effects on biofilm formation, motility, adhesion, and invasion.ConclusionThis study demonstrated that fimC acts as an atypical DNA-binding protein to regulate the transcription of agn43. It also highlights the importance of fimC in the biofilm formation and adhesion ability of APEC, which provides new insights into the functions of the fimbrial chaperone protein FimC.